Beberapa Faktor Yang Berpengaruh Terhadap Keluhan Nyeri Punggung Bawah Pada Penjual Jamu Gendong - Pratiwi H, Mayrika; Setyaningsih, Yuliani; Kurniawan, Bina; Martini, Martini (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2009)
Background: Herbal Tonic Beverage Carriers are considered as high risk group of low backpain occurrence due to their activities such as bending position, lifting and carrying heavy loads. This study aims to analyze factors influencing low back pain occurrence among herbaltonic beverage carriers.Method: It was a cross sectional analytical study involved 30 herbal tonic beverage carriers in Geneng Village, Mijen Sub-district, District of Demak. Chi-square and logistic regression were employed as analysis tools.Result: This study found that age (p=0.355), working period (p=1.000), duration of lifting (p=0.433), weight of load (p=0.029) and lifting technique (p=0.628) have no correlation with low back pain occurrence. Multivariate analysis showed that sitting position was the only factor which predicts the occurrence of low back pain. Regarding this finding, it isrecommended for herbal tonic beverage carriers to have a better working position during their works in order to prevent their vertebrae from injury.Keyword : Low back pain, herbal tonic beverage carriers